Managing for a change. Management of development projects a guide for community groups: workbook - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The handbook describes in simple terms the stages and procedures that can be followed by a group to manage a community development project successfully, it is not a textbook, but a guide to assist a group to make its own decisions on managing its project. The types of community projects are so varied that it is not possible to give examples to cover all eventualities. The examples in the Handbook are therefore used to illustrate general ideas. The contents of the chapters in the Handbook are in the same order as those in the workbook. So while an understanding of the general procedures can be obtained from the Handbook, they can immediately be applied to the group's project with the aid of the workbook. While the handbook describes in simple terms the general principles, the workbook is designed to assist you to manage your own project. No answers are provided in the workbook, only questions. However, the questions have been devised so that you ask and answer them at the appropriate time. The workbook is not there to test or trap you; it is provided to assist you by suggesting questions that should be considered when a group manages a community development project